Global Geoscience - Canada's Link with the World - Barr, Sandra (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY Geoscience is a global discipline, and geoscientists are typically world travellers who recognize the need for effective international collaboration. Canadian geoscientists, in particular, have a long history of active participation in international geoscience organizations and efforts. A notable example is the Association of Geoscientists for International Development (AGID), which was founded in Canada in 1974. Canadians are credited in establishing AGID, and have been prominent throughout its history. Other examples include the International Geological Congress, the International Union of Geological Sciences, and the International Geoscience Program (IGCP). The global nature of geoscience is demonstrated in research, the mineral and petroleum industries, and natural hazards prediction and mitigation. In spite of this global awareness within the geosciences, the importance of geoscience to the well-being of Earth and its inhabitants is not widely appreciated. International efforts to address this issue include activities such as the International Year of Planet Earth, but more must be done by granting agencies, societies such as the Geological Association of Canada, and individual geoscientists.